Quantum error-correcting codes: the unit design strategy. (2018) - Hurley, Ted; Hurley, Donny; Hurley, Barry
A series of maximum distance quantum error-correcting codes are developed and analysed. For a given rate and given error-correction capability, quantum error-correcting codes with these specifications are constructed. The codes are explicit with efficient decoding algorithms. For a given field maximum length quantum codes are constructed.